The effects of different types of Tai Chi exercises on motor function in patients with Parkinson's disease: A network meta-analysis - Lei, Honghui; Ma, Zhen; Tian, Kexin; Liu, Ke; Wang, Jiaying; Zhu, Xiangyu; Mi, Baohong; Chen, Ying; Yang, Qihao; Jiang, Huili (Frontiers in Aging Neuroscience, 2022)
Background Tai Chi can show improvement in balance and motor ability of elderly patients with PD. However, there were few reports on differences in outcomes associated with different types of Tai Chi on improving exercise capacity in elderly patients with PD. We compared the improvement of motor function in Parkinson's patients with different types of Tai Chi, for finding an optimal intervention. Methods The following databases were searched from the beginning of the establishment of each database to 10 January 2022: PubMed, EMBASE, The Cochrane Library, CNKI, Wanfang Database, and VIP Database. Randomized controlled trials incorporating different types of Tai Chi for PD were included. The outcome measures were UPDRSIII and BBS. NMA was conducted using Stata 15.0 based on a frequentist framework. Results A total of twenty trials were eligible, including 996 participants. In conventional meta-analysis, as for the UPDRSIII scale, 24-form simplified Tai Chi (SMD = −1.272, 95% CI [−2.036, −0.508], P < 0.05, I2 > 50%), Tai Chi exercise program (SMD = −0.839, 95% CI [−1.828, 0.151], P > 0.05, I2 > 50%), 8-form simplified Yang style Tai Chi (SMD = −0.325, 95% CI [−1.362, 0.713], P > 0.05, I2 > 50%), and 8-form simplified Chen style Tai Chi (SMD = −0.28, 95% CI [−0.97, 0.42], P > 0.05, I2 > 50%) were statistically more efficient than the control group. For BBS outcome, 24-form simplified Tai Chi (MD = 3.979, 95% CI [3.364, 4.595], P < 0.05, I2 <50%), Tai Chi exercise program (MD = 5.00, 95% CI [2.07, 7.93], P > 0.05, I2 > 50%), and 8-form simplified Chen style Tai Chi (MD = 1.25, 95% CI [0.52, 1.98], P < 0.05, I2 > 50%) were better than the control group. In the network meta-analysis, the results of UPDRSIII were as follows: 24-form > TCEP > 8-form YS > 8-form CS > control. The ranking probability of BBS was as follows: TCEP > 24-form > 8-form CS > control. Conclusion Among the four treatments studied, 24-form Tai Chi and Tai Chi exercise programs have shown better efficacy than other types. Our study provides new insights into exercise therapy for PD and may contribute to the formulation of a clinical exercise prescription. Systematic review registration Identifier: CRD42021285005.